(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the level of satisfaction among patients after undergoing inpatient surgical treatment for uterine fibroids at the Obstetrics Department of Quang Ninh Obstetrics and Pediatrics Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 84 patients. Data were collected using a standardized questionnaire issued under Decision No. 3869/QĐ-BYT (2019), applying a five-point Likert scale. Results: Overall patient satisfaction was found to be very high across all assessed dimensions: accessibility (mean score ranging from 4.83 ± 0.37 points to 4.89 ± 0.31 points), transparency of information and treatment procedures (100%), facility infrastructure and service amenities (4.89 ± 0.31 points to 4.96 ± 0.18 points), attitude and professional competence of healthcare staff (4.89 ± 0.31 points to 4.96 ± 0.18 points), and overall service delivery (4.88 ± 0.32 points to 4.92 ± 0.25 points). Conclusion: Patients who underwent surgical treatment for uterine fibroids at the Obstetrics Department of Quang Ninh Obstetrics and Pediatrics Hospital reported a very high level of satisfaction (100%) across all service-related dimensions evaluated.